PERBAIKAN ULANG TATA LETAK IKM DIANEKA FURNITURE DI KOTA DUMAI - Fitra; Imam Faizal; Mhd.Rizky Ramadhan; Wahyu Ari Setiawan (Jurnal Mitra Teknik Industri, 2025)
Dianeka Furniture, a small-scale industry located in South Dumai, is experiencing inefficiencies in its production facility layout, characterized by irregular workflow, long material handling distances, and poor workspace utilization. These issues have led to decreased production efficiency and increased waste of time and labor. This research aims to redesign the facility layout in a more systematic and efficient manner to support smoother production processes and improve productivity. The methods applied in this study are Systematic Layout Planning (SLP) and the Graph-based method, focusing on the analysis of activity relationships and material movement distances. Data were collected through direct observation, interviews, and documentation of production activities. The results show that the proposed layout using the SLP method reduced the total material handling distance from 121 units to 97.8 units. Meanwhile, the layout generated using the Graph-based method achieved even better results, reducing the total distance to 96.2 units, which represents a 13.7% reduction compared to the initial layout. In addition to minimizing material movement, the proposed layouts also improved workflow and space utilization. Therefore, the Graph-based method proved to be more effective in optimizing the facility layout at Dianeka Furniture and can serve as a strategic solution to enhance operational efficiency and overall productivity.